Study Of Financial Performance Of Telekom Malaysia For Ten Years (1996-2005) - Tanggau@Albert, Daven (2008)
This paper examines the financial performance of Telekom Malaysia for ten years from year 1996 to 2005. the study used vertical analysis, horizontal analysis, Altman\'s Z score and various financial ratios to evaluate the performance of Telekom Malaysia. These various methods were used to valuate each fincial statement such as income statement, balance sheet and cash flow.